Tinjauan Hukum Pidana Islam terhadap Tindak Pidana Penipuan - Hasibuan, Nahda; Panjaitan, Budi Sastra; Sativa, Annisa (Sekolah Tinggi Ilmu Hukum Prof Gayus Lumbuun, 2024)
Islam forbids all forms of criminal acts including all forms of criminal acts of fraud. Fraud is a crime committed by someone by lying to other people or deception. When viewed from the point of view of the actions and elements contained in fraud, there are similarities between criminal acts of fraud and criminal acts regulated in Islamic law, namely: ghulul, treason, and lying. The research approach used is normative legal research. The purpose of this research is to find out the views of Islamic criminal law on fraud crimes with the following conclusions: In Islamic criminal law the punishment given to perpetrators of fraud is jariman ta'zir because ta'zir is a punishment handed over to the government (ulul amri) especially the judge who imposed the criminal sentence, the judge can determine the type of punishment according to his ijtihad such as the crime of fraud which has been regulated in Article 378 of the Criminal Code. Keywords: Islamic Criminal Law and Fraud.